2020
DOI: 10.1371/journal.pone.0232603
|View full text |Cite
|
Sign up to set email alerts
|

Refining LNA safety profile by controlling phosphorothioate stereochemistry

Abstract: Drug discovery with phosphorothioate oligonucleotides is an area of intensive research. In this study we have controlled the stereochemistry of the phosphorothioate backbone of LNA oligonucleotides to investigate the differences in safety profile, target mRNA knock down, and cellular uptake in vitro. The study reveals that controlling only four stereocenters in an isomeric phosphorothioate mixture can improve the therapeutic index significantly by improving safety without compromising activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Phosphorothioate (PS) modification of (oligo)­nucleotides is one of the most frequently used synthetic approaches for investigating nucleic acid metabolism or for improving the pharmacokinetics of therapeutic or diagnostic molecules. Many applications of thio-modified oligonucleotides, such as the elucidation of ion-binding sites on RNA and identification of phosphate sites important for ligand or protein binding or for catalysis, assume that this modification has little or no effect on the secondary structure of nucleic acids. However, it has been shown that incorporation of the PS moiety alters the negative charge distribution and can significantly alter the conformation of nucleic acids, thus changing their biological activity. , Furthermore, substitution of a nonbridging oxygen in the phosphate residue with sulfur usually generates an additional stereogenic center at the phosphorus atom yielding a pair of diastereomers, , which are often differentially recognized by specific proteins or enzymes. Interestingly, a natural PS backbone modification was shown to be an epigenetic mark in bacterial DNA, and recently it was also found in both prokaryotic and eukaryotic rRNAs …”
Section: Introductionmentioning
confidence: 99%
“…Phosphorothioate (PS) modification of (oligo)­nucleotides is one of the most frequently used synthetic approaches for investigating nucleic acid metabolism or for improving the pharmacokinetics of therapeutic or diagnostic molecules. Many applications of thio-modified oligonucleotides, such as the elucidation of ion-binding sites on RNA and identification of phosphate sites important for ligand or protein binding or for catalysis, assume that this modification has little or no effect on the secondary structure of nucleic acids. However, it has been shown that incorporation of the PS moiety alters the negative charge distribution and can significantly alter the conformation of nucleic acids, thus changing their biological activity. , Furthermore, substitution of a nonbridging oxygen in the phosphate residue with sulfur usually generates an additional stereogenic center at the phosphorus atom yielding a pair of diastereomers, , which are often differentially recognized by specific proteins or enzymes. Interestingly, a natural PS backbone modification was shown to be an epigenetic mark in bacterial DNA, and recently it was also found in both prokaryotic and eukaryotic rRNAs …”
Section: Introductionmentioning
confidence: 99%
“…Hence, strategies using oligonucleotides with a limited number of PS linkages have gained traction, presumably as such oligonucleotides have fewer/weaker protein interactions [104]. One additional concern with PS modifications is the introduction of stereoisomerism to the structure, which may also be a complicating factor in toxicity [105]. The ZEN end-modified anti-miRs with 2 0 -OME modifications avoid such stereoisomeric complexity, confer nuclease resistance and appear relatively safe [72], [71], and perhaps offer a more straightforward route to robust stereodefined anti-miRs over PS alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…LNA amidites were dissolved at 0.1 M in MeCN. Synthesis was performed as described previously [ 20 ].…”
Section: Methodsmentioning
confidence: 99%